Pengembangan Bahan Ajar Al-Qur’an Hadits Dalam Meningkatkan Sikap Sosial Siswa di MTsN Persiapan 3 Padangsidimpuan - Muhammad Yusuf Tanjung; Zulhimma Zulhimma; Zainal Efendi Hasibuan (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2025)
The learning of Qur’an and Hadith plays a significant role in shaping students’ character and social attitudes. However, at MTsN Persiapan 3 Padangsidimpuan, there are still challenges such as limited teaching materials and insufficient media to support students' understanding of social values. This study aims to develop Qur’an and Hadith instructional materials to improve students’ social attitudes using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase identified students’ needs, followed by the design of instructional materials based on Qur’anic and Hadith values. The development stage included expert validation and limited trials. Implementation was carried out with Grade VII students. Validation results indicated the materials were highly valid: subject matter experts (93.1%), media experts (94%), and language experts (93.1%). The practicality was also high, with positive responses from students (81%) and Qur’an-Hadith teachers (87.5%). The effectiveness of the materials in enhancing social attitudes—such as empathy, cooperation, and social responsibility—was very satisfactory, with a score of 2.220 and a percentage of 85.3%. Therefore, the developed instructional materials are considered appropriate and effective for use in Qur’an and Hadith learning at MTsN Persiapan 3 Padangsidimpuan.